Weaving traditional ecological knowledge into thematic interpretation in park guiding in Sarawak national parks / Victor Luna Anak Amin - Amin, Victor Luna (2019)
A plethora of studies for past decade believed that the application of traditional ecological knowledge (TEK) can help improved natural resource management and environmental conservation practices, but little is known regarding its interpretive communication potential in enhancing vistors experience, promoting positive attitudes and shaping on-site visitor behaviour in the context of park guiding service in ecotourism settings in national parks. This experimental research, underpinned by the TORE model of interpretation and informed research, investigated the efforts of park guides to examine whether a training-workshop on TEK theme-based interpretive guided tour could influence visitors’ cognitive, affective and behavioural outcomes of interpretation in four selected Sarawak’s national parks. An experimental quantitative research technique was adopted by employing descriptive analysis, paired t-test and Pearson product-moment correlation analysis. The training-workshop elicits park guides’ competency gaps and reactions to the training-workshop through pre-post selfassessment and post-training self-administered questionnaires (n=81) and visitors’ outcomes of guided tours through self-administered questionnaire (n = 380) immediately after each tour ended. The study indicated that, TEK theme-based guided tour training, can successfully delivered the knowledge and skills required by park guides to help improve their capacity to effectively enhance visitor experience, promote appreciative attitudes, and influence their behaviour. The findings also illustrated that the weaving of TEK as the topic, themes and self-enforced rules in well presented thematic interpretive guided tour in ecotourism settings, appeared to have improved its impacts in making a difference in how visitors think, feel and behave with respect to things or resources of the national parks the park guides had interpreted. The study concluded that the weaving of TEK into thematic interpretation, if well planned and presented, can help park guides and park managers improve visitors’ experience and better achieve the protection and conservation objectives. Future empirical studies should replicate in other national parks to determine if these findings are consistent across other national parks of socio-economically unequal, culturally and religiously diverse. Other study should also further predict the key target constructs or identifying key “drivers” constructs on the effects of TEK themebased guided tour in a more adaptive approach.